2002
DOI: 10.1111/1467-8527.00230
|View full text |Cite
|
Sign up to set email alerts
|

The Gulliford Lecture: Reciprocal working by education, health and social services: lessons for a less‐travelled road

Abstract: The 2001 Gulliford Lecture was given by Professor Roy McConkey, of the University of Ulster. In this article, based on his lecture, Roy McConkey reflects on some of the themes in Ron Gulliford’s work from the 1960s. These themes still seem relevant to our work with pupils and students with special educational needs today. Roy McConkey focuses, in particular, on collaboration between practitioners from different professional backgrounds. He invites the reader to reflect on some of the strengths of current pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Moreover, this view of inclusion is consistent with the view that an inclusive school should represent the ethos of community involvement (Bayliss, 1995c;Friend & Bursuck, 1996;McConkey, 2002;Reid, 2005). It is by embracing community involvement and participation that every individual can appreciate the diversity and individual qualities of others.…”
supporting
confidence: 77%
“…Moreover, this view of inclusion is consistent with the view that an inclusive school should represent the ethos of community involvement (Bayliss, 1995c;Friend & Bursuck, 1996;McConkey, 2002;Reid, 2005). It is by embracing community involvement and participation that every individual can appreciate the diversity and individual qualities of others.…”
supporting
confidence: 77%
“…In the present study, it seems that the lack of a specific framework for collaboration in the legislation and daily practice was the most important barrier to integrating the services, as many other writers have argued (McCartney 2000;McConkey 2002). Connecting the policies to the daily practice in the schools which we visited, it is evident that schools are left to decide individually on the model of collaboration between people from different disciplines.…”
Section: Discussionmentioning
confidence: 60%
“…However, as some parents noted, the value of these plans would be strengthened if other services had been party to the process, such as schools and career guidance, so that issues beyond the remit of the project could be tackled (Allen, Foster-Fishman, & Salem, 2002). Recent research has demonstrated the value of cross-agency, person-centred planning (Robertson et al, 2006) but it has proved elusive to implement given the fragmentation in British services among education, social services, health and the voluntary sector (McConkey, 2002).…”
Section: Discussionmentioning
confidence: 99%